Right hepatectomy for colonic cancer unique metastasis - Peyroulou, Alfredo; do Campo, Magela; Correa, Waldemar; Castiglioni, Juan C (Cirugía del Uruguay, 1983)
A case of right hepatectomy for metacronous unique colonic cancer metastasis is presented. An historical review and foundation of metatatic liver resection criteria are done.